Educação de adultos e comunidades quilombolas - SILVA, Alexandre Santos da (2017)
It is defended the idea that being and doing adult education can be understood here in this study as a type of differentiated teaching and very well articulated, from the pedagogical point of view, than other types of teaching. One of the methodological differences and objectives of the schools that attend adult education in relation to other teaching modalities involves specific action of the professional teaching from the use of the dialectic, predicted and validated in the pedagogical planning of many teachers. Considering that the process of adult social integration, especially when it comes from quilombola communities, was a strategic point of analysis in this research, focusing on the pedagogical performance of students enrolled in youth and adult education classes (EJA ), remnants of quilombola communities, enrolled in the Municipal Polo School of Primary Agricultural Education Maurício Machado, in which was verified the actions and impacts of the cultural knowledge interferences of the quilombola communities in the pedagogical dynamic of the school curriculum in Adult Education (EJA). This study analyzed the actions and impacts of the cultural knowledge interferences of the quilombola communities, located along the District of Caraparu in the Municipality of Santa Izabel do Pará, in the pedagogical dynamics developed in that school through the curriculum, focusing on social action in terms of planning, methodology and objectives achieved in the proposal of adult education. For the data collection, it was necessary to formulate the results of this research using the following methods: inductive to observe the facts about the cultural interferences of the quilombola communities in the EJA; the statistical method for collecting numerical data of the population involved; historical method to find theoretical basis in the documentary and bibliographic sources related to the research theme; monographic, because the research was carried out in a school that serves quilombola communities. The technique used in the field research was accomplished based on the direct documentation, applying the interview. We also chose the use of extensive direct observation with the use of questionnaires and also the indirect documentation with the use of documentary analysis. Therefore, this study emphasized that, in practical terms, the use of cultural knowledge from quilombola communities, articulated in the school context, both through teaching didactic action, as well as through curriculum, or even through the Political and Pedagogical Project due to the student inserted in the modality of education of adults, confirm the richness of the dynamic between the elements that are attributed to the meanings in face of what one intends to construct in terms of learning through the idea that involves the existing elements in a new dimension developed by the student based on his cognitive action that develops both in the school and in his community.